2020
DOI: 10.1371/journal.pone.0240692
|View full text |Cite
|
Sign up to set email alerts
|

The selective PGI2 receptor agonist selexipag ameliorates Sugen 5416/hypoxia-induced pulmonary arterial hypertension in rats

Abstract: Pulmonary arterial hypertension (PAH) is a lethal disease characterized by a progressive increase in pulmonary artery pressure due to an increase in vessel tone and occlusion of vessels. The endogenous vasodilator prostacyclin and its analogs are used as therapeutic agents for PAH. However, their pharmacological effects on occlusive vascular remodeling have not been elucidated yet. Selexipag is a recently approved, orally available and selective prostacyclin receptor agonist with a non-prostanoid structure. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…For IV TRE, we used a dose infusion rate of 810 ng/kg/min that was based upon data from a previous study in Su/Hx-challenged rats (Chaudhary et al, 2018) and demonstrated acute pulmonary vasodilation in our experiments. Furthermore, based upon previously published data in Su/Hx challenged rats, an oral dosing frequency of 30 mg/kg selexipag administered BID was selected (Honda et al, 2020) with pulmonary vasodilation at this dose observed up to 4 h in our acute Hx challenged rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For IV TRE, we used a dose infusion rate of 810 ng/kg/min that was based upon data from a previous study in Su/Hx-challenged rats (Chaudhary et al, 2018) and demonstrated acute pulmonary vasodilation in our experiments. Furthermore, based upon previously published data in Su/Hx challenged rats, an oral dosing frequency of 30 mg/kg selexipag administered BID was selected (Honda et al, 2020) with pulmonary vasodilation at this dose observed up to 4 h in our acute Hx challenged rats.…”
Section: Discussionmentioning
confidence: 99%
“…The dose selection for the compounds tested was based upon a combination of published data (Chaudhary et al, 2018;Honda et al 2020) and efficacy studies in healthy rats measuring the inhibition of pulmonary vasoconstriction induced by challenge with an inhaled hypoxic mixture (Corboz et al, 2021c).…”
Section: Introductionmentioning
confidence: 99%
“…This current study followed an established Su/Hx protocol. 25 After the disease had been established (baseline), the rats were then treated with drugs or vehicles for further 3 weeks. Our Su/Hx rat model replicated the lower RVEF observed in a modified Su/Hx mouse protocol carried 22 as well as within clinic in PAH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Selexipag reduces right ventricular systolic pressure and attenuates pulmonary vascular remodeling in concert with reducing proliferative vascular smooth muscle cells in monocrotaline or Sugen 5416/hypoxia‐induced PH in rats. 18 , 19 , 20 Selexipag is rapidly absorbed after oral administration and hydrolyzed to its active metabolite MRE‐269 ({4‐[(5,6‐diphenylpyrazin‐2‐yl)(isopropyl)amino]butoxy}acetic acid; also known as ACT‐333679). MRE‐269 has more potent activity and a longer half‐life than selexipag; therefore, it is considered to be the major contributor to the pharmacological activity of the drug.…”
Section: Introductionmentioning
confidence: 99%